2017
DOI: 10.1136/bmjresp-2017-000252
|View full text |Cite|
|
Sign up to set email alerts
|

Differentiation of quantitative CT imaging phenotypes in asthma versus COPD

Abstract: IntroductionQuantitative CT (QCT) imaging-based metrics have quantified disease alterations in asthma and chronic obstructive pulmonary disease (COPD), respectively. We seek to characterise the similarity and disparity between these groups using QCT-derived airway and parenchymal metrics.MethodsAsthma and COPD subjects (former-smoker status) were selected with a criterion of post-bronchodilator FEV1 <80%. Healthy non-smokers were included as a control group. Inspiratory and expiratory QCT images of 75 asthmati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
3

Relationship

3
7

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 36 publications
(42 reference statements)
3
38
0
Order By: Relevance
“…Another potential limitation is the absence of chest computed tomography measurements of the airways and lung parenchyma. These measurements are providing new insights into lung diseases in general and airflow limitation in particular [11].…”
mentioning
confidence: 99%
“…Another potential limitation is the absence of chest computed tomography measurements of the airways and lung parenchyma. These measurements are providing new insights into lung diseases in general and airflow limitation in particular [11].…”
mentioning
confidence: 99%
“…In fact, the airways remodeling is commonly observed in asthma, and it is characterized by radiological signs such as thickening of the bronchial wall [81][82][83][84], bronchial dilations [85], mucus plug, and air trapping. Several studies supported by the Severe Asthma Research Program showed that these radiological signs are associated with a more severe disease [81][82][83][86][87][88][89][90][91][92], until to real clinical -radiological clusters [93]. Despite some literature correlating radiological imaging and asthma, at the time being few clinical trials showed a relationship between bronchiectasis and disease severity.…”
Section: Imagingmentioning
confidence: 99%
“…Cluster analysis of clinical variables by Burgel et al (10) concluded that COPD patients with similar airflow obstruction may belong to different phenotypes and may differ in symptoms, outcomes, age and comorbidities. Besides clinical variables, qCT imaging-based machine learning of diseased lungs has advanced recently, and multiscale imaging-based cluster analyses have provided clinically meaningful clusters in both asthma and COPD cohorts (11)(12)(13)(14). By considering inter-site and inter-subject variations through normalization schemes (15,16), their approach enabled the analysis of datasets acquired by multiple centers utilizing multiple make and model CT scanners.…”
Section: Introductionmentioning
confidence: 99%